2009
DOI: 10.2535/ofaj.86.89
|View full text |Cite
|
Sign up to set email alerts
|

Modulation mechanism of c-mpl promoter activity in megakaryoblastic cells

Abstract: Summary: Thrombopoietin receptor (c-Mpl) is considered to regulate megakaryocytopoiesis. In this study, we investigated an effect of activation of a protein kinase C (PKC) on c-mpl promoter activity to elucidate the underlying mechanisms of c-mpl gene expression in megakaryoblastic cells. PKC is a member of a family of serine/threonine protein kinases in the cytosol involved in cell growth and differentiation. Phorbol 12-myristate 13-acetate (PMA) is known as PKC activator, significantly enhanced the c-mpl pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It was recently reported that the promoter activity of c-mpl was upregulated by TPO pretreatment and TPO-induced c-mpl promoter activity was modulated at transcription level through a PKC-dependent pathway in the CMK cells (Sunohara et al, 2003 11) , 2004 12) ). In this research, we investigated the role of GATA promoter element in TPO-induced c-mpl gene expression through a PKC-independent pathway by using a transient transfection assay system.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was recently reported that the promoter activity of c-mpl was upregulated by TPO pretreatment and TPO-induced c-mpl promoter activity was modulated at transcription level through a PKC-dependent pathway in the CMK cells (Sunohara et al, 2003 11) , 2004 12) ). In this research, we investigated the role of GATA promoter element in TPO-induced c-mpl gene expression through a PKC-independent pathway by using a transient transfection assay system.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously (Sunohara et al, 2003 11) , 2013 13) , 2009 14) , 2010 15) , 2008 16) ), the cells were cultured in RPMI 1640 medium (GIBCO, Grand Island, NY) containing 10% FCS, 2mM L-glutamine, 100 units/ml penicillin, 100µg/ ml streptomycin, and 0.25 µg/ml amphotericin B at 37 °C in humid air containing 5% CO 2 atmosphere. CMK cells were cultured in RPMI 1640 medium (GIBCO, Grand Island, NY) supplemented with 10% fetal calf serum (FCS), 2mM L-glutamine, 100 units/ml penicillin, 100 µg/ ml streptomycin, and 0.25 µg/ml amphotericin B at 37 °C in humidified air containing 5% CO 2 atmosphere.…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations